2004
DOI: 10.1111/j.0013-9580.2004.47003.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Impact of Anxiety, Depression, and Clinical Seizure Features on Health‐related Quality of Life in Epilepsy

Abstract: Summary:Purpose: To determine the independent effects of depression and anxiety on health-related quality of life (HRQOL) in epilepsy as well as the relative explanatory power of psychiatric comorbidity compared with demographic and clinical epilepsy variables (e.g., seizure frequency, severity, and chronicity).Methods: Subjects (n = 87) with temporal lobe epilepsy completed self-report measures of depression, anxiety, HRQOL, and seizure severity. Information was derived regarding subjects' seizure frequency, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
268
1
31

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 460 publications
(331 citation statements)
references
References 38 publications
31
268
1
31
Order By: Relevance
“…Similarly to some studies 10 , no significant difference was found in the QoL due to the other socio-demographic aspects studied, although other papers 5,[7][8][9]15 reported that an elevated age and low scholastic level were related to a worse QoL.…”
Section: Qol and The Socio-demographic And Clinical Aspectssupporting
confidence: 53%
See 3 more Smart Citations
“…Similarly to some studies 10 , no significant difference was found in the QoL due to the other socio-demographic aspects studied, although other papers 5,[7][8][9]15 reported that an elevated age and low scholastic level were related to a worse QoL.…”
Section: Qol and The Socio-demographic And Clinical Aspectssupporting
confidence: 53%
“…Some studies describe an association between poly-therapy and a worse QoL 10,26,27 , particularly in the dimension of seizure worry, which represents a concern with the occurrence of ES, apprehension about possible traumatisms and the social effects of the unpredictability of the ES. However, other studies did not observe this association 8,16 . On the other hand, some authors question the ability to evaluate the impact of AED on the QoL, since this aspect has a very small impact on calculation of the scores in the QOLIE-31 26 .…”
Section: Qol and The Socio-demographic And Clinical Aspectsmentioning
confidence: 76%
See 2 more Smart Citations
“…In that study, more than twice as many children with epilepsy (20% compared to 9% of control) reported suicidal ideation. Interictal psychiatric symptoms adversely influence the health-related quality of life to a greater extent than the frequency, severity and chronicity of seizures [7]. Consideration of the psychiatric comorbidities in treatment decisions involving drug selection has been discussed for both adult [8] and pediatric [9] patients with epilepsy.…”
Section: Introductionmentioning
confidence: 99%